Discharge Against Medical Advice in Emergency Department: Literature Review - Risa Herlianita; Indri Wahyuningsih (PT FORMOSA CENDEKIA GLOBAL, 2022)
Discharge against medical advice (DAMA) can lead to death or morbidity. This study was conducted to examine research papers on discharge against medical advice in the emergency department. Method: The articles published between January 1, 2012, and January 31, 2022, from Scopus, Pubmed database, and Google Scholar were studied using literature review, data visualization tools, and sophisticated text analysis. As a result, 17 of the 20.095 scientific articles found were authored using the keywords discharge against medical advice AND emergency. This review occupied VOSviewer programs for creating a visualization of large sets of data to uncover keyword clusters and theme structures in titles, keywords, and abstracts. In the field of nursing, studies on DAMA are rather rare. The analyses showed three main themes namely overview DAMA, the impact, and the reason for DAMA. As a result, the findings can aid present and future research on this topic by providing information about the networks, trends, and contents of the literature.